Swear Words In Comment Column Of X Application About The 2024 Presidential Election In Indonesia - Ketut Budi Aryani (Journal of English Language Learning, 2024)
Language is very important for every people because by using language people can communicate with each other in daily life. There are a lot studies that discuss language, one of them is swear word. Swear words are one of the language phenomena found in society. Swear words were also found in the utterances uttered by social media users. This research is qualitative descriptive research. Data was taken from comments from posts that exposed the 2024 presidential election. The data collection method used observation. The instruments for this research are the researcher, smartphone and observation sheet. The results of the study show that religion swear words were found 4 number occurrences with a percentage of 7.54%, excrement swear words were 5 with a percentage of 9.43%, 10 animal swear words were found with a percentage of 18.87%, 20 swear words for Mental Illness were found with a percentage of 37.73%, sex swear words and personal background had the same number occurrence, namely 7 with a percentage of 13.20% so that overall there were 53 swear words found. Future, researchers are advised to research swear words in other applications to get to know more about the swear words spoken by social media users on social media.